Accreditation-Based Assistant Leadership Model and Spiritual Values in Academic Service - Mobonggi, Arten; Solong, Najamuddin Petta; Muda, Lisdawati; Hasbi, Muh.; Wantu, Hasyim Mahmud (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research is important because the servant leadership model is crucial in supporting accreditation and is infused with spiritual values to optimize academic services. This research applies the accreditation-based servant leadership model and spiritual values in academic services at the IAIN Sultan Amai Gorontalo Postgraduate program. This field research uses a descriptive qualitative approach, with data collected through interviews, observations, and documentation, and then analyzed through data reduction and presentation to conclude. The study concludes that the servant leadership model can only support accreditation by applying spiritual values, especially Islamic ones, in academic services. Every academic service requires a strong spirit, which cannot be separated from spiritual values derived from the truth of revelation. Integrated work activities, serving as a means of communication and sharing program information and academic issues supported by academic information systems, are recognized as encouraging timely studies and academic achievements of students and lecturers. However, this will not be complete without spiritual values such as patience, gratitude, sincerity, humility (tawadhu), information and communication technology as God's gifts, and prayer.